Absolute energy levels in nanodiamonds of different origins and surface chemistries - Miliaieva, Daria; Djoumessi, Aurelien Sokeng; Čermák, Jan; Kolářová, Kateřina; Schaal, Maximilian; Otto, Felix; Shagieva, Ekaterina; Romanyuk, Olexandr; Pangrác, Jiří; Kuliček, Jaroslav; Nádaždy, Vojtech; Stehlík, Štěpán; et al. (Nanoscale advances, 2023)
Nanodiamonds (NDs) are versatile, broadly available nanomaterials with a set of features highly attractive for applications from biology over energy harvesting to quantum technologies. Via synthesis and surface chemistry, NDs can be tuned from the sub-micron to the single-digit size, from conductive to insulating, from hydrophobic to hydrophilic, and from positively to negatively charged surface by simple annealing processes. Such ND diversity makes it difficult to understand and take advantage of their electronic properties. Here we present a systematic correlated study of structural and electronic properties of NDs with different origins and surface terminations. The absolute energy level diagrams are obtained by the combination of optical (UV-vis) and photoelectron (UPS) spectroscopies, Kelvin probe measurements, and energy-resolved electrochemical impedance spectroscopy (ER-EIS). The energy levels and density of states in the bandgap of NDs are correlated with the surface chemistry and structure characterized by FTIR and Raman spectroscopy. We show profound differences in energy band shifts (by up to 3 eV), Fermi level position (from p-type to n-type), electron affinity (from +0.5 eV to -2.2 eV), optical band gap (5.2 eV to 5.5 eV), band gap states (tail or mid-gap), and electrical conductivity depending on the high-pressure, high-temperature and detonation origin of NDs as well as on the effects of NDs' oxidation, hydrogenation, sp2/sp3 carbon phases and surface adsorbates. These data are fundamental for understanding and designing NDs' optoelectrochemical functional mechanisms in diverse application areas.